Young Consumer Loyalty of Luxury Products - Praswati, Aflit Nuryulia; Alfathana, Aziz; Sina, Helmia Khalifah (Prosiding University Research Colloquium, 2022)
This study aims to analyze the effect of brand image and brand trust on brand loyalty through customer satisfaction. This research was conducted on students using the branded shoes at the Muhammadiyah University of Surakarta by using a total sample of 115 respondents. The sampling technique is probability sampling. The data analysis technique used was SEM-PLS whose calculations were assisted by the SmartPLS 3.2.2 program. The evaluation analysis of the Partial Least Square (PLS) model is carried out by evaluating the outer model and evaluating the inner model. The results of data analysis show that brand image and brand trust have a positive and insignificant effect on brand loyalty. Then brand image and brand trust have a significant positive effect on customer satisfaction. Furthermore, customer satisfaction has a significant positive effect on brand loyalty. And the results of data analysis also show that customer satisfaction mediates the effect of brand image and brand trust on brand loyalty.